1994
DOI: 10.1164/ajrccm.149.4.8143062
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fenoterol exposure increases in vivo and in vitro airway responses in guinea pigs.

Abstract: We tested the hypothesis that the regular inhalation of a beta 2-adrenergic receptor (beta 2AR) agonist increases airway responsiveness in guinea pigs. A potent beta 2AR agonist, fenoterol hydrobromide, in sublaryngeal doses equivalent to maximal doses used in the treatment of asthma on a weight basis (5.28 micrograms/kg), was administered by nebulizer three times a day for 6 weeks to normal adolescent guinea pigs (FEN, n = 10) and to ovalbuminsensitized guinea pigs challenged twice weekly with ovalbumin (OA +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 28 publications
3
25
2
Order By: Relevance
“…We found that prolonged exposure of human bronchi to fenoterol affects maximal efficacy of ET-1 but not its potency. Our results are in agreement with the work reported by Wang and colleagues (60), who showed that chronic fenoterol exposure increased maximal airway response to ACh but not ACh EC 50 in guinea pigs. Potency of an agonist depends in part on the affinity of receptors for binding the agonist and in part on the efficiency with which agonist-receptor interaction is coupled to response.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that prolonged exposure of human bronchi to fenoterol affects maximal efficacy of ET-1 but not its potency. Our results are in agreement with the work reported by Wang and colleagues (60), who showed that chronic fenoterol exposure increased maximal airway response to ACh but not ACh EC 50 in guinea pigs. Potency of an agonist depends in part on the affinity of receptors for binding the agonist and in part on the efficiency with which agonist-receptor interaction is coupled to response.…”
Section: Discussionsupporting
confidence: 94%
“…Studies in animals and humans showed that chronic exposure to fenoterol or salbutamol induces a nonspecific bronchial sensitization, whereas the relaxant effects of these ␤ 2 -agonists on the airway smooth muscle are not decreased (11,59,60). The bronchial sensitization induced by fenoterol is similar to the sensitization provoked by ovalbumin in sensitized guinea pigs (60). Chronic administration of salbutamol at low doses to guinea pigs increases airway reactivity to histamine and methacholine (11).…”
mentioning
confidence: 99%
“…Few experimental studies have investigated the effects of ß 2 -agonists on the inflammatory response in animal models of chronic allergic inflammation. The inhalation of environmental allergens is a major mechanism of asthma, and experimental models with allergen-induced chronic airway inflammation are probably more relevant to the study of the mechanisms of human asthma than models with a single challenge (19). In a previous study, we assessed the effects of airway inflammation induced by repeated OVA aerosol exposures in guinea pigs (16).…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs the regular use of ß 2 -agonists induces airway narrowing and an increase in smooth muscle contractility (19). This treatment can also contribute to the increase of bronchial responsiveness (9) due to the reduction of constitutive adrenergic effects by either receptor down-regulation and/or decrease of receptor turnover, both reducing the receptor density on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, the airway smooth muscle appears to have a special resistance to β 2 -adrenergic desensitization, probably due to a rapid turnover of the β 2 -adrenergic receptors [21]. Some studies, using low or medium doses, failed to find desensitization of the guinea pig trachea, although they demonstrated an increase in the response to metacholine or acetylcholine after in vivo salbutamol [22]or in vivo and in vitro fenoterol [23]treatment of guinea pigs. Moreover, an increase in airway responsiveness to indirectly acting stimuli after regular treatment with salbutamol or terbutaline has been described in asthmatic patients [24, 25].…”
Section: Discussionmentioning
confidence: 99%